2020
DOI: 10.1101/2020.02.14.948398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal fluid metabolomics identifies 19 brain-related phenotype associations

Abstract: Advances in technology have allowed for the study of metabolomics in the context of disease, enabling the discovery of new potential risk factors, diagnostic markers, and drug targets. For neurological and psychiatric phenotypes, the cerebrospinal fluid (CSF) is of particular biomedical importance as it is in direct contact with the brain and spinal cord. However, the CSF metabolome is difficult to study on a large scale due to the relative complexity of the procedure needed to collect the fluid compared to bl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 103 publications
(85 reference statements)
4
16
0
Order By: Relevance
“…Consistent with previous mQTL studies(citations 40,41,6467), the top SNP associated with levels of methyl-lysine, rs4539242, is in high linkage disequilibrium (LD) with both the missense mutation M461T (R 2 =1.0 in Europeans) and synonymous mutation F484F (R 2 =0.94 in Europeans), observations that represent an internal quality control for the present analysis (Manhattan plots and LocusZoom in Figure 2.B-C , respectively). Both mutations are themselves associated with levels of methyl-lysine (p=4.22×10 −13 and p=1.28×10 −44 , respectively; Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous mQTL studies(citations 40,41,6467), the top SNP associated with levels of methyl-lysine, rs4539242, is in high linkage disequilibrium (LD) with both the missense mutation M461T (R 2 =1.0 in Europeans) and synonymous mutation F484F (R 2 =0.94 in Europeans), observations that represent an internal quality control for the present analysis (Manhattan plots and LocusZoom in Figure 2.B-C , respectively). Both mutations are themselves associated with levels of methyl-lysine (p=4.22×10 −13 and p=1.28×10 −44 , respectively; Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 92%
“…In A , for the top GWA hits we generated box and whisker plots based on metabolite abundances as a function of allele variance across all genetic ancestries in this study. Consistently with previous mQTL studies, 40,41,6567 polymorphisms in the exonic region coding for the enzyme PYROXD2 were associated with variance in the levels of methyl-lysine, an observation that represents a sort of internal quality control for the present analysis compared to the literature. Manhattan plots and LocusZoom are shown in panels B-C , respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Among methods to investigate brain metabolism, metabolomics remains a powerful tool to offer insights at the tissue and cellular level by measuring hundreds of metabolites. Metabolomics studies revealed the association of brain metabolism with physiological activities and disease conditions (118122), and when combined with genome-wide association studies can be particularly useful in predicting specific diseaseassociated metabolites (123). Fluxomics, the measurement of flow of metabolites between different pathways, better enables investigation into the cellular metabolic state.…”
Section: Regulators Of Sex Differences In Brain Immunometabolismmentioning
confidence: 99%
“…The genome-wide significant SNPs (p < 5 × 10 −8 ) from a previous genome-wide meta-analysis of CSF metabolites [19] were extracted for each elastic net-selected metabolite (5863 SNPs for 52 metabolites). These SNPs (or the top 100 SNPs if there were more than 100 genome-wide significant SNPs for a metabolite) were used as instrumental variables (IV) for the metabolite in an MR analysis for each elastic net-selected metabolite-NTK biomarker association pair in the combined WRAP and Wisconsin ADRC cohort.…”
Section: Mendelian Randomizationmentioning
confidence: 99%